Hydrophilic and Functionalized Nanographene Oxide Incorporated Faster Dissolving Megestrol Acetate - Mohammad Saiful Islam; Faradae Renner; Kimberly Foster; Martin S. Oderinde; Kevin Stefanski; Somenath Mitra (Molecules, 2021)
The aim of this work is to present an approach to enhance the dissolution of progestin medication, megestrol acetate (also known as MEGACE), for improving the dissolution rate and kinetic solubility by incorporating nano graphene oxide (nGO). An antisolvent precipitation process was investigated for nGO-drug composite preparation, where prepared composites showed crystalline properties that were similar to the pure drug but enhanced aqueous dispersibility and colloidal stability. To validate the efficient release profile of composite, in vitro dissolution testing was carried out using United States Pharmacopeia, USP-42 paddle method, with gastric pH (1.4) and intestinal pH (6.5) solutions to mimic in vivo conditions. Pure MA is practically insoluble (2 µg/mL at 37 °C). With the incorporation of nGO, it was possible to dissolve nearly 100% in the assay. With the incorporation of 1.0% of nGO, the time required to dissolve 50% and 80% of drug, namely T50 and T80, decreased from 138.0 min to 27.0 min, and the drug did not dissolve for 97.0 min in gastric media, respectively. Additionally, studies done in intestinal media have revealed T50 did not dissolve for 92.0 min. This work shows promise in incorporating functionalized nanoparticles into the crystal lattice of poorly soluble drugs to improve dissolution rate.